Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1142/s0218810415400043
|View full text |Cite
|
Sign up to set email alerts
|

Bone Grafts for Scaphoid Nonunion: An Overview

Abstract: The scaphoid is the most common fractured bone in the wrist. Despite adequate non-surgical treatment, around 10% to 15% of these fractures will not heal. Untreated scaphoid non-union can cause a scaphoid non-union advance collapse (SNAC), this is a progressive deformity and can cause degenerative changes in the wrist. Surgery is focused on achieving consolidation, pain reduction and a good position of the scaphoid while preventing osteoarthritis in the long-term. Surgery consists of reduction and fixation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 38 publications
0
20
0
5
Order By: Relevance
“…Die Wahl der Operationsmethode ist nach wie vor ein Diskussionsthema [14]. Bei adäquater konservativer Behandlung konsolidieren 10 -15 % der im mittleren Drittel lokalisierten Kahnbeinfrakturen nicht, wobei proximale Polfrakturen sogar bis zu 30 % nicht heilen [7,8].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Die Wahl der Operationsmethode ist nach wie vor ein Diskussionsthema [14]. Bei adäquater konservativer Behandlung konsolidieren 10 -15 % der im mittleren Drittel lokalisierten Kahnbeinfrakturen nicht, wobei proximale Polfrakturen sogar bis zu 30 % nicht heilen [7,8].…”
Section: Introductionunclassified
“…Eine persistente Pseudarthrose führt innerhalb von 10 Jahren in 100 % der Fälle zu einer progressiven Arthrose, welche von einer radiokarpalen Arthrose bis zur manifesten, kompletten Handgelenksarthrose reicht und als SNAC-Wrist (Scaphoid Non-union Advanced Collaps) bezeichnet wird [7,10]. Je länger der Zeitabstand zwischen dem Frakturereignis und der operativen Versorgung beträgt, desto höher ist das Risiko der Arthroseentwicklung [4,11].…”
Section: Introductionunclassified
“…5 Scaphoid nonunions (SNUs) always require surgery. 6 Many techniques that require bone graft have been suggested. 6,7 The biological activity of platelet-rich plasma (PRP) on bone healing has been described.…”
Section: Introductionmentioning
confidence: 99%
“…6 Many techniques that require bone graft have been suggested. 6,7 The biological activity of platelet-rich plasma (PRP) on bone healing has been described. [8][9][10] The use of PRP in delayed unions and nonunions has already been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated the utility of this graft. 8 All were first fixed using headless screw fixation with a screw from the Acutrak 2 system (Acumed, Hillsboro, Oregon, United States) according to the manufacturer's instructions. The intraoperative decision regarding fixation with or without supplementary KWs was made by the treating surgeon according to the degree of stability felt to be obtained following reduction, bone grafting, and insertion of the screw.…”
Section: Introductionmentioning
confidence: 99%